Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

A scalable consensus docking decision-support pipeline for aquaculture bridging foodomics and affordability - Chen-Hsun Liu; Chiu-Hui Kuo; William Chih-Wei Chang; Chih-Hsuan Fan; Bonien Chen; Li-Lian Liu; Fen-Chen Wu; Pao-Chi Liao; Kuohsun Chiu (Computers and Electronics in Agriculture, 2026)

New features of Peristediidae fishes in the South China Sea - Han Tian; Hsuan‐Ching Ho; Pan Liu; Mingting Li; Wei Xie; Yane Jiang; Xingle Guo; Jiajie Chen; Junpeng Yang; Kedong Yin (Journal of Fish Biology, 2026)
Deep‐diving surveys enable observations of new features of behavioural and functional dimensions of the fish that are typically missing from specimen‐based taxonomy. This study documents three rare armoured searobins (Peristediidae: Scalicus engyceros , Paraheminodus murrayi , Peristedion liorhynchus ) in Xianbei Seamount, Zhongsha Islands and Shenhu Canyon in the South China Sea. Not seen in the dead specimen, the fish in life exhibits bizarre shrimp‐like (in common sense) morphology: the lip barbels formed a laterally rake‐like structure, and the pectoral fins functioned as legs that literally ‘walked’ on the sediment. The fish S. engyceros showed both sideways and backward walking. The paired pectoral fins extrude outwards laterally like flat plates, supporting body balance during walking and swimming. When disturbed, individuals escaped rapidly using both pectoral appendages and tail fins, combining shrimp‐like jerky movements with typical fish swimming. The same species have been reported to occur in both the North and South Pacific oceans, suggesting that their oceanic distribution is by larval dispersal via oceanic currents such as equatorial and Indonesian throughflow currents. The co‐occurrence of three congeners in the same sea may hint local geographic speciation at work after settlement in a seamount habitat.

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Differential metabolomic shifts in jellyfish tissues exposed to artificial light spectra - Bonien Chen; Chiu-Hui Kuo; Chen-Hsun Liu; Yung-Kuo Lee; Jui-Kuo Kao; Chih-Hsuan Fan; Feng-Cheng Wu; Li-Lian Liu; Kuohsun Chiu; Yu-Yun Chen (Science of The Total Environment, 2026)

A two-span vehicle-bridge interaction system integrating a two-axle vehicle for vehicle scanning method - Judy P. Yang; Li-Hsuan Chen (Engineering Structures, 2026)

Stationary-Phase Antimicrobial Peptide Production in Escherichia coli - Wei-Sheng Yu; Ming-Hung Chen; Chia-Li Ting; Wen-Hsuan Tsung; Pei-Yu Sun; Po-Yu Liu; Si-Yu Li (Probiotics and Antimicrobial Proteins, 2026)

Biological safety assessment of dissolved aluminum ions in coastal seawater: acute toxicity effects on Pacific whiteleg shrimp (Litopenaeus vannamei) Post-larvae - Pei-Hsuan Wu; Yen-Kung Hsieh; Tsang-Hsieh Hung; Wei-Shan Chou; Ya-Rung Wu; Ping Chen; Jin-Li Yu; Chao-Kai Kang (Ecotoxicology, 2026)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Social-ecological memories as references for biodiversity restoration and conservation action in coastal community - Chia-Hsuan Hsu; Yu-Wen Wu; Jiefeng Kang; Hung-Kai Chiu; Mei-Ching Li; Wei-Ting Chen (Marine Pollution Bulletin, 2025)

Prediction of expected maximum moment strength for reinforced concrete columns with normal and high-strength materials under varying axial load ratios - Mu-Hsuan Li; Nguyen Van Bao Nguyen; Yu-Chen Ou; Tung-Chun Tsai (Engineering Structures, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Precision monitoring of rice nitrogen fertilizer levels based on machine learning and UAV multispectral imagery - Ming-Der Yang; Yu-Chun Hsu; Yi-Hsuan Chen; Chin-Ying Yang; Kai-Yun Li (Computers and Electronics in Agriculture, 2025)

Metal plate reduction produces self-assembled graphene hydrogel for flexible all-carbon solid-state supercapacitors - Yen-Hsuan Li; Yu-Hsuan Ho; Jui-Chin Lee; I-Wen Peter Chen (Chemical Engineering Journal, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Immune responses in giant groupers after vaccination with inactivated bivalent vaccine against betanodavirus and ranavirus - Yu-Hsuan Kai; Chun-Kuei Chang; Hong-Qi Li; Wei-Hsu Chen; Shau-Chi Chi; Yu-Chi Wu (Aquaculture, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Rapid tear screening of diabetic retinopathy by a detachable surface acoustic wave enabled immunosensor - Dhrubajyoti Das; Hsuan-An Chen; Chao-Li Weng; Yung-Chun Lee; Sheng-Min Hsu; Jae-Sung Kwon; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Accelerating flow simulations in the built environment by using the fast fluid dynamics initializer - Chi Zhang; Chih-Yung Wen; Yu-Hsuan Juan; Yee-Ting Lee; Zhengwei Chen; An-Shik Yang; Zhengtong Li (Building and Environment, 2024)

Proprioceptive and olfactory deficits in individuals with Parkinson disease and mild cognitive impairment - Kuan-yi Li; Kristen A. Pickett; Hsuan-wei Fu; Rou-shayn Chen (Acta Neurologica Belgica, 2024)
Background Individuals with neurodegenerative diseases such as Parkinson disease (PD) and Alzheimer’s (AD) disease often present with perceptual impairments at an early clinical stage. Therefore, early identification and quantification of these impairments could facilitate diagnosis and early intervention. Objectives This study aimed to compare proprioceptive and olfactory sensitivities in individuals diagnosed with PD and mild cognitive impairment (MCI). Methods Proprioception in the forearm and olfactory function were measured in neurotypical older adults, individuals with PD, and individuals with MCI. Position and passive motion senses were assessed using a passive motion apparatus. The traditional Chinese version of the University of Pennsylvania smell identification test (UPSIT-TC) and the smell threshold test (STT) were used to identify and discriminate smell, respectively. Results Position sense threshold between the groups differed significantly ( p p p = 0.004) groups showing significantly higher than the control group. The control group had significantly higher mean UPSIT-TC scores than the PD ( p p = 0.006) groups. The control group had a significantly lower mean STT threshold than the PD and MCI groups ( p p = 0.008, respectively). UPSIT-TC scores significantly correlated with disease progression in PD (r = − 0.50, p = 0.008) and MCI (r = 0.44, p = 0.04). Conclusions Proprioceptive and olfactory sensitivities were reduced in individuals with PD and MCI, and these deficits were related to disease severity. These findings support previous findings indicating that perceptual loss may be a potential biomarker for diagnosing and monitoring disease progression in individuals with neurodegenerative diseases.

A computed tomography radiomics-based model for predicting osteoporosis after breast cancer treatment - Yu-Hsuan Lai; Yi-Shan Tsai; Pei-Fang Su; Chung-I Li; Helen H. W. Chen (Physical and Engineering Sciences in Medicine, 2024)
Many treatments against breast cancer decrease the level of estrogen in blood, resulting in bone loss, osteoporosis and fragility fractures in breast cancer patients. This retrospective study aimed to evaluate a novel opportunistic screening for cancer treatment-induced bone loss (CTIBL) in breast cancer patients using CT radiomics. Between 2011 and 2021, a total of 412 female breast cancer patients who received treatment and were followed up in our institution, had post-treatment dual-energy X-ray absorptiometry (DXA) examination of the lumbar vertebrae and had post-treatment chest CT scan that encompassed the L1 vertebra, were included in this study. Results indicated that the T-score of L1 vertebra had a strongly positive correlation with the average T-score of L1–L4 vertebrae derived from DXA (r = 0.91, p < 0.05). On multivariable analysis, four clinical variables (age, body weight, menopause status, aromatase inhibitor exposure duration) and three radiomic features extracted from the region of interest of L1 vertebra (original_firstorder_RootMeanSquared, wavelet.HH_glcm_InverseVariance, and wavelet.LL_glcm_MCC) were selected for building predictive models of L1 T-score and bone health. The predictive model combining clinical and radiomic features showed the greatest adjusted R 2 value (0.557), sensitivity (83.6%), specificity (74.2%) and total accuracy (79.4%) compared to models that relied solely on clinical data, radiomic features, or Hounsfield units. In conclusion, the clinical-radiomic predictive model may be used as an opportunistic screening tool for early identification of breast cancer survivors at high risk of CTIBL based on non-contrast CT images of the L1 vertebra, thereby facilitating early intervention for osteoporosis.

The sub-nanometer In2O clusters on Ag nanoparticles with highly selective electrochemical CO2 reduction to formate - Dinesh Bhalothia; Hsiao-Yun Liu; Shih-Hsuan Chen; Yao-Tien Tseng; Wenbo Li; Sheng Dai; Kuan-Wen Wang; Tsan-Yao Chen (Chemical Engineering Journal, 2024)

A proposed framework for a social-ecological traits database for studying and managing urban plants and assessing the potential of database development using Floras - Chi-Ru Chang; Mong-Huai Su; Yi-Hsuan Li; Ming-Chun Chen (Urban Forestry & Urban Greening, 2024)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Design and assembly of Ag-decorated Bi2O3 @ 3D MXene Schottky heterojunction for the highly permeable and multiple-antifouling of fibrous membrane in the purification of complex emulsified oil pollutants - Yingqing Zhan; Ximin Chen; Ao Sun; Hongshan Jia; Yucheng Liu; Lingli Li; Yu-Hsuan Chiao; Xulin Yang; Fei Zhu (Journal of Hazardous Materials, 2023)

Unusual promotion/inhibition effect of polyethylenimine on CO2/CH4 hydrate formation: A potential green chemical additive for CH4-CO2 replacement process - Yu-Hsuan Ho; Yau Zu Khoo; Yan-Ping Chen; Ryo Ohmura; Li-Jen Chen (Chemical Engineering Journal, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Rat Hair Metabolomics Analysis Reveals Perturbations of Unsaturated Fatty Acid Biosynthesis, Phenylalanine, and Arachidonic Acid Metabolism Pathways Are Associated with Amyloid-β-Induced Cognitive Deficits - Tian-Hoe Tan; Shih-Wen Li; Chih-Wei Chang; Yuan-Chih Chen; Yu-Hsuan Liu; Jui-Ti Ma; Ching-Ping Chang; Pao-Chi Liao (Molecular Neurobiology, 2023)
Hair is a noninvasive valuable biospecimen for the long-term assessment of endogenous metabolic disturbance. Whether the hair is suitable for identifying biomarkers of the Alzheimer’s disease (AD) process remains unknown. We aim to investigate the metabolism changes in hair after β-amyloid (Aβ 1-42 ) exposure in rats using ultra-high-performance liquid chromatography-high-resolution mass spectrometry–based untargeted and targeted methods. Thirty-five days after Aβ 1-42 induction, rats displayed significant cognitive deficits, and forty metabolites were changed, of which twenty belonged to three perturbed pathways: (1) phenylalanine metabolism and phenylalanine, tyrosine, and tryptophan biosynthesis— l -phenylalanine, phenylpyruvate, ortho-hydroxyphenylacetic acid, and phenyllactic acid are up-regulated; (2) arachidonic acid (ARA) metabolism—leukotriene B4 (LTB4), arachidonyl carnitine, and 5(S)-HPETE are upregulation, but ARA, 14,15-DiHETrE, 5(S)-HETE, and PGB2 are opposite; and (3) unsaturated fatty acid biosynthesis— eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), FA 18:3 + 1O, and FA 18:3 + 2O are downregulated. Linoleic acid metabolism belonging to the biosynthesis of unsaturated fatty acid includes the upregulation of 8-hydroxy-9,10-epoxystearic acid, 13-oxoODE, and FA 18:2 + 4O, and downregulation of 9(S)-HPODE and dihomo-γ-linolenic acid. In addition, cortisone and dehydroepiandrosterone belonging to steroid hormone biosynthesis are upregulated. These three perturbed metabolic pathways also correlate with cognitive impairment after Aβ 1-42 stimulation. Furthermore, ARA, DHA, EPA, l -phenylalanine, and cortisone have been previously implicated in the cerebrospinal fluid of AD patients and show a similar changing trend in Aβ 1-42 rats’ hair. These data suggest hair can be a useful biospecimen that well reflects the expression of non-polar molecules under Aβ 1-42 stimulation, and the five metabolites have the potential to serve as novel AD biomarkers.

Exogenous Methylglyoxal Ameliorates Source Strength and Retrieves Yield Loss Under Drought Stress During Grain Filling in Maize - Yi-Hsuan Lin; Yu-Ka Jin; Zhen-Yuan Chen; Zu-Dong Xiao; Si Shen; Shun-Li Zhou (Journal of Plant Growth Regulation, 2023)

Evaluation of wetting measures and capture efficiencies of fugitive dust emitted from a limestone pile: Experiments and artificial neural network - Po-Hsuan Yen; Justus Kavita Mutuku; Chung-Shin Yuan; Wei-Hsiang Chen; Chih-Cheng Wu; Chien-Sen Li (Process Safety and Environmental Protection, 2023)

A new approach to modeling pre-symptomatic incidence and transmission time of imported COVID-19 cases evolving with SARS-CoV-2 variants - Sam Li-Sheng Chen; Grace Hsiao-Hsuan Jen; Chen-Yang Hsu; Amy Ming-Fang Yen; Chao-Chih Lai; Yen-Po Yeh; Tony Hsiu-Hsi Chen (Stochastic Environmental Research and Risk Assessment, 2023)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

A multi-attribute decision-making model for improving inefficient industrial parks - Sheng-Hau Lin; Danyang Wang; Xianjin Huang; Xiaofeng Zhao; Jing-Chzi Hsieh; Gwo-Hshiung Tzeng; Jia-Hsuan Li; Jia-Tsong Chen (Environment, Development and Sustainability, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Methane Seeps and Independent Methane Plumes in the South China Sea Offshore Taiwan - Susan Mau; Tzu-Hsuan Tu; Marius Becker; Christian dos Santos Ferreira; Jhen-Nien Chen; Li-Hung Lin; Pei-Ling Wang; Saulwood Lin; Gerhard Bohrmann (Frontiers in Marine Science, 2020)

Computational comparison of bone cement and poly aryl-ether-ether-ketone spacer in single-segment posterior lumbar interbody fusion: a pilot study - Chih-Wei Chang; Yu-Hsuan Chung; Chia-Jung Chang; Yen-Nien Chen; Chun-Ting Li; Chih-Han Chang; Yao-Te Peng (Physical and Engineering Sciences in Medicine, 2020)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Life cycle toxicity assessment of earthworms exposed to cadmium-contaminated soils - Wei-Yu Chen; Wen-Hsuan Li; Yun-Ru Ju; Chung-Min Liao; Vivian Hsiu-Chuan Liao (Ecotoxicology, 2017)

Conditional Probabilities for Large Events Estimated by Small Earthquake Rate - Yi-Hsuan Wu; Chien-Chih Chen; Hsien-Chi Li (Pure and Applied Geophysics, 2016)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

Integrated water resources system dynamics modeling and indicators for sustainable rural community - Yuan-Hua Li; Pei-Yuan Chen; Wei-Hsuan Lo; Ching-Pin Tung (Paddy and Water Environment, 2015)

Regulation of phenylalanine ammonia-lyase (PAL) gene family in wood forming tissue of Populus trichocarpa - Rui Shi; Christopher M. Shuford; Jack P. Wang; Ying-Hsuan Sun; Zhichang Yang; Hsi-Chuan Chen; Sermsawat Tunlaya-Anukit; Quanzi Li; Jie Liu; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Protection by chrysin, apigenin, and luteolin against oxidative stress is mediated by the Nrf2-dependent up-regulation of heme oxygenase 1 and glutamate cysteine ligase in rat primary hepatocytes - Chin-Shiu Huang; Chong-Kuei Lii; Ai-Hsuan Lin; Yu-Wen Yeh; Hsien-Tsung Yao; Chien-Chun Li; Tsu-Shing Wang; Haw-Wen Chen (Archives of Toxicology, 2013)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Inactivation of Staphylococcus aureus and Escherichia coli in Water Using Photocatalysis with Fixed TiO2 - Chih-Yu Chen; Li-Chun Wu; Hsuan-Yu Chen; Ying-Chien Chung (Water, Air, & Soil Pollution, 2010)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)